Busuu: a Mobile Applications - Ginting, Doriani Romboni (The Explora, 2023)
In the age of technological advancement, gadget has an important role in the various activities of aperson, no exception in learning. With a variety of applications offered by platform providers, bothandroid and iOS. Now one can learn something independently. Busuu is an application developedto help a person in learning foreign languages independently, such as learning Arabicindependently. Learning paths used in this application have been using international standards,ranging from beginner level (A1), basic level (A2), intermediate level (B1), and advanced (B2).This application provides learning materials in the form of audio visual that can improve the fourskills of English language. Optimizing the usage of Busuu applications is very likely to preparesomeone to be able to communicate in English.